Nutrition made clear - Anding, Roberta; Teaching Company (Chantilly, Va. : Teaching Co., 2009)
Provides an overview of fundamental nutrition concepts and the science underlying them.
Part 3: Disc 5. Lecture 25. Nutrition and digestive health ; Lecture 26. Prebiotics and probiotics in your diet ; Lecture 27. Food safety: it's in your hands ; Lecture 28. Demystifying food labels ; Lecture 29. Facts on functional foods ; Lecture 30. A look at herbal therapy -- Disc 4. Lecture 31. Organic or conventional: your choice ; Lecture 32. Fake or real: sugars and fats ; Lecture 33. Creating your own personal nutrition plan ; Lecture 34. Exercise and nutrition: partners for life ; Lecture 35. The future of nutrition: science and trends ; Lecture 36. Nutrition facts and FAQs.
DVD.
Taught by Professor Roberta H. Anding, Baylor College of Medicine and Texas Children's Hospital.
Course No. 1950.
36 lectures (30 minutes each)
In three containers (26 x 5 x 19 cm.) each.
Includes bibliographical references (p. 143-157).
Keywords: Nutrition; Diet; Diet; Nutritional Physiological Phenomena